Cystic fibrosis in South Africa: spectrum of disease, diagnosis, and determinants of outcome - Zampoli, Marco (Department of Paediatrics and Child Health, 2024)
Cystic fibrosis (CF) occurs with varying incidence in all populations throughout the world but much less is known about the epidemiology and outcomes of CF in low-or-middle income countries (LMIC) compared with high income settings. Continued improvement in CF-related outcomes and survival witnessed in the past decades is attributed to multiple factors yet sub-optimal quality of CF care, and limited CF diagnosis capacity continue to exist in most LMIC, including South Africa (SA). CF treatment and prognosis have been transformed by the recent introduction of highly effective cystic fibrosis transmembrane conductance regulator modulator drugs (CFTRm). However, access to these transformative drugs for those with eligible genotypes is currently limited to high-income countries. Understanding the clinical spectrum of CF in SA and investigating novel techniques to diagnose CF is important to advocate for improved quality of CF care including CFTRm drugs. The overall aim of this work was to document the spectrum and outcomes of CF in South Africans and to investigate more sensitive measures to diagnose CF and CFTR-related disorders in this population. The studies included in this thesis are divided into two components. This first component comprises observational cohort studies derived from a single-centre CF clinic dataset in Cape Town, SA, and the nation-wide South African CF registry, which was established in 2018 in preparation for this thesis. The CF registry cohort in SA was then compared in a cross-sectional study to a matched Canadian CF registry cohort, and differences in lung function and nutrition outcomes adjusted for known factors. The second component was a prospective study investigating the feasibility and diagnostic utility of the novel β-adrenergic sweat test in a cohort of South Africans with inconclusive CF diagnosis. The chapters of this thesis are presented as published manuscripts, which collectively address the overall aim of this body of work. The SA CF registry in its first year of inception captured a total of 447 people with CF across both private and public health sectors. Summary demographic descriptions of the cohort include median age of 14.7 years with self-identified White race making up 70% of the CF population, followed by Mixed-race ancestry (19%) and Black Africans (10%). Genotype pattern mirrored ancestry with F508del is the most common variant in Whites and people with Mixed-race ancestry, and 3120+1G>A (class I) the most common variant in Black Africans. Overall, 81% of people with CF (pwCF) in SA have at least one copy of F508del and are, thus, eligible for elexacaftor/tezacaftor/ivacaftor. A key finding of the registry-based studies was that lung function and nutrition outcomes in SA were significantly lower across all ages compared with Canada, attributed to differences in the quality of CF care and social determinants of CF health between the two countries. In SA, poor nutrition was the strongest factor independently associated with severe lung disease and was more prevalent in people living in lower 10 socioeconomic conditions, including people who were not White. Another key finding was despite significant improvement in overall CF survival at a single centre in Cape Town over the past 40 years, disparities between race groups still exist in SA with increased risk of mortality observed in young children who were not White. People with Black African ancestry, who form the majority of the SA population, are likely to be underrepresented in the SA CF registry, raising concern that CF is being missed or underdiagnosed in the majority of South Africans. Furthermore, the genotype of Black Africans means that none are eligible for CFTRm, which has serious implications for future treatment. These registry-based studies highlight disparities in CF care and outcomes both within SA and compared with a high-income setting – novel findings because SA is one of only a few LMIC with CF registries. Addressing these disparities affecting people with CF in SA will require interventions such as greater awareness of CF in SA, universal newborn screening for CF, focused attention on improving nutrition and overall improvement in the quality of essential CF care, especially as LMIC have disproportionally more pwCF who are ineligible for CFTRm drugs. The diagnosis of CF using standard approaches may remain inconclusive in a small proportion of individuals, which leads to unnecessary anxiety for families and inappropriate treatment where people do not actually have CF or a CFTR-related disorder. Furthermore, accurate diagnosis of CF is important for research and submission of registry data. The β-adrenergic sweat test was proposed as an easier alternative to other electrophysiological measurements of CFTR function such as nasal potential difference and intestinal current measurements, which are not available in SA. We therefore conducted a study evaluating this hypothesis in adult subject controls, and 32 individuals (mostly children) whose CF diagnosis was inconclusive. Key findings of this study were that the β-adrenergic sweat was superior to sweat chloride test in excluding CF in the majority of subjects and that βadrenergic sweat secretion in children was lower compared to adults. Implications and novelty of this research are that existing reference ranges for this test may not be applicable in children, and confirmation that the β-adrenergic sweat test is a viable alternative for measuring CFTR function. A number of families benefited from this study by reversal of their incorrect CF diagnosis. The overriding finding and impact of this work has been to highlight disparities in diagnosis, treatment, and outcomes of CF within SA and in the global context. The current status of CF care in SA mirrors many other LMIC that share similar challenges and barriers to improving CF care, including access to affordable CFTRm drugs. The findings of this thesis have made valuable contributions to local and global advocacy initiatives to improve CF care and access to CFTR drugs for many thousands of pwCF living in LMIC who are being left behind in this new era of CF treatment.